Discourse 2.0 : language and new media - Tannen, Deborah; Trester, Anna Marie (Georgetown University Round Table on Languages and Linguistics series, 2013)
Our everyday lives are increasingly being lived through electronic media, which are changing our interactions and our communications in ways that we are only beginning to understand. In this book, the editors have teamed up with top scholars in the field to shed light on the ways language is being used in, and shaped by, these new media contexts. Topics explored include: how Web 2.0 can be conceptualized and theorized; the role of English on the worldwide web; how use of social media such as Facebook and texting shape communication with family and friends; electronic discourse and assessment in educational and other settings; multimodality and the "participatory spectacle" in Web 2.0; asynchronicity and turn-taking; ways that we engage with technology, including reading on-screen and on paper; and how all of these processes interplay with meaning-making.